The Role of BPJS Employment Improving Worker Welfare in Indonesia - Evlin Novianti Tambunan; Habieb Pahlevi; Yasir Riady (Contemporary Journal of Applied Sciences, 2025)
BPJS Ketenagakerjaan (Employment Social Security Agency) has an important role in Improving Workers' Welfare in Indonesia. This role is realized through various Social Security Programs designed to protect workers from socioeconomic risks that may occur while they are working in Indonesia. One of them is providing social protection to workers, increasing a sense of security in working, encouraging equal distribution of welfare, supporting national economic growth, and providing education and awareness of social security. With this Qualitative Descriptive Research using secondary data, namely data obtained from references in the form of journals, writings, websites, and other sources.